Extraction and embryo morphology of Bursera bipinnata (Burseraceae) - Ramos-Ordoñez, María Felix; del Coro Arizmendi, María; Flores-Enríquez, Valeria; Márquez-Guzmán, Judith (Instituto de Ecología, A.C., 2016)
Background and Aims: The understanding of the reproductive biology of plants, from the formation of the seed to its establishment, allows the development of different conservation strategies. In the genus Bursera, whose main center of diversification is Mexico, the diaspore is a pyrene formed by a strongly lignified endocarp enclosing the seed. The anatomical characteristics of the pyrene and the parthenocarpy are the main factors that have hindered the study of embryogenesis and the development of propagation techniques. In this paper we describe the morphology of the Bursera bipinnata embryo, extracted by a technique that does not alter the structure or the chemical composition of tissues.Methods: During the beginning of the dispersal stage 2014, we collected unripe fruits and pyrenes with exposed pseudaril. Unripe fruits were fixed in FAA. A low speed micromotor with handpiece was used. A conical burr was used in unripe fruits to scabble the fruit valves. To open the pyrenes a diamond disc was used. After opening the endocarp, embryos were removed and fixed.Key results: The pattern of development coincides with other model species of angiosperms. In immature fruits globular, heart-shaped, torpedo and cotyledonary stages were observed, the latter in early stages. During the torpedo stage, cotyledons branch into three lobes and are spliced, as they grow, they are folded upon themselves, and cover the embryonic axis; however, the radicular meristem is always exposed.Conclusions: The extraction technique is rapid, inexpensive and non-destructive to tissues, having a potential use in the detailed analysis of embryogenesis in the genus Bursera, tissue culture and ex situ conservation.